Answer:
- 8pq-3pq= 5pq
- 2m-3m+4 =4-m
Step-by-step explanation:
- The first equation shows two terms can be combine as follow: 8pq-3pq= (8-3)pq by applying common factoring. Then, because 8-3=5, it can be expressed as 5pq.
- In the second equation, we have only two terms that can be factored by combining the terms that share the same factor (which is m). Then, 2m-3m+4 can be expressed like m(2-3)+4. Because (2-3)=-1 and because the order of the sum does not affect the result, the result is 4-m.
Answer:
3.08 km/h.
Step-by-step explanation:
We know that,
Ali traveled at a speed of s km/h for 2.5 hours.
Let d be the distance and t be the time.
...(1)
On his return journey, he increased his speed by 4 km/h and saved 15 minutes. So, distance is d and times is t-15.
...(2)
From (1) and (2), we get
Put t=40 in (1).
So, t=40 and d=100.
Now,
Total distance = d + d = 100 + 100 = 200
Total time = t + t - 15 = 40 + 40 - 15 = 65
So, the average speed is
Therefore, the average speed is 3.08 km/h.
Answer:
y ≈ 5.2
Step-by-step explanation:
∠ F = 180° - (42 + 48)° ← sum of angles in a triangle
∠ F = 180° - 90° = 90°
Thus Δ DEF is right at F
Using the sine ratio in the right triangle
sin48° =
=
=
( multiply both sides by 7 )
7 × sin48° = y , then
y ≈ 5.2 ( to the nearest tenth )
Answer:
i don't understand this and i'm in high school how is this possible????????????
Step-by-step explanation:
Answer:
1000000000000000000001
Step-by-step explanation:
Done. You're welcome